2000
DOI: 10.1021/ma000528o
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering of Dilute Hydrophobically Modified Alkali-Soluble Emulsion Solutions:  Effects of Hydrophobicity and Spacer Length of Macromonomer

Abstract: A novel comb water-soluble associative polymer (hydrophobically modified alkali-soluble emulsion (HASE)), comprising of a random copolymer of methacrylic acid (MAA), ethyl acrylate (EA), and 1 mol % of hydrophobically modified macromonomers, was studied using laser light scattering and rheological techniques. The hydrophobic substituents are separated from the backbone by a poly(ethylene glycol) (PEG or PEO) spacer chain. The hydrophobicity of the hydrophobic substituents and the length of PEO spacers control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…These results are consistent with DLS studies performed by other authors, in which two decay modes in diluted HMWSP solutions have also been reported and also associated to the presence of both single chain objects, with or without intramolecular hydrophobic bonds and multichain aggregates. This is in particular the case for Dai et al [25][26][27] working on Hydrophobically modified Alkali Soluble Emulsions (HASE) made of random copolymers of methacrylic acid and ethyl acrylate with 1 mol% of various ethoxylated alkyl hydrophobic monomers, Sato et al [15] working on random copolymers of acrylic acid and N-dodecylmethacrylamide at rather high molar fractions (5 to 30 mol%), Vidal et al [35] working on carboxymethylcellulose modified with 1 to 6 mol% randomly distributed N,N-dihexylamine side-groups and Alami et al [36], working on polyethylene oxyde endcapped with C12 chains. However, to our knowledge, DLS evidence of aggregates in diluted solutions of random HMWSP with SPAM backbones is reported here for the first time.…”
Section: Dynamic Light Scatteringmentioning
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with DLS studies performed by other authors, in which two decay modes in diluted HMWSP solutions have also been reported and also associated to the presence of both single chain objects, with or without intramolecular hydrophobic bonds and multichain aggregates. This is in particular the case for Dai et al [25][26][27] working on Hydrophobically modified Alkali Soluble Emulsions (HASE) made of random copolymers of methacrylic acid and ethyl acrylate with 1 mol% of various ethoxylated alkyl hydrophobic monomers, Sato et al [15] working on random copolymers of acrylic acid and N-dodecylmethacrylamide at rather high molar fractions (5 to 30 mol%), Vidal et al [35] working on carboxymethylcellulose modified with 1 to 6 mol% randomly distributed N,N-dihexylamine side-groups and Alami et al [36], working on polyethylene oxyde endcapped with C12 chains. However, to our knowledge, DLS evidence of aggregates in diluted solutions of random HMWSP with SPAM backbones is reported here for the first time.…”
Section: Dynamic Light Scatteringmentioning
confidence: 82%
“…Various techniques have been implemented among which viscosimetry [4][5][6][7][8][9][10][11][12], fluorescence [13][14][15][16], transmission, scanning and environmental scanning electron microscopy (TEM, SEM and ESEM) [16][17][18], 19 F NMR spectroscopy [19,20], neutron scattering [21][22][23][24] and Static and Dynamic Light Scattering (SLS and DLS) [14][15][16][25][26][27][28][29][30][31][32][33][34][35][36][37]. Theoretical approaches have also been proposed to describe HMWSP static [38,39] and dynamic [40] properties.…”
Section: Nomenclaturementioning
confidence: 99%
“…The reduction in the aggregation number in this low concentration regime reduces the lifetime of the polymer system as indicated by the shifting of fast relaxation peak to lower time as depicted in Figure 7(a and b). Such behavior was also detected by dynamic light scattering technique performed on HASE systems, 34,35 where the correlation length between the hydrophobic junctions decreases with increasing polymer concentration. This behavior was pictorially presented in Figure 8, where the concentration is increased from cluster overlapping concentration, C*, to established network concentration, C**.…”
Section: Dynamic and Relaxation Behaviormentioning
confidence: 82%
“…The slower chain reptation will lead to the formation of longer multiple relaxation times observed in the polymer system as shown in the relaxation spectra. This behavior is proposed in Figure 8 34,35 for concentration greater than the established network concentration C**.…”
Section: Dynamic and Relaxation Behaviormentioning
confidence: 83%
“…Understanding the nature of associative thickener interactions and their effects on rheology has been the focus of numerous studies. A vast majority of these studies focused on HEUR (hydrophobically modified, ethoxylated urethanes), [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] HASE (hydrophobically modified, alkali-swellable emulsions), 1,4,10,11,[19][20][21][22][23][24][25][26] and HMHEC (hydrophobically modified, hydroxyethyl cellulose) 1,4,27-31 associative thickener types. There is very little information available on another class of associative thickeners, HEAT (hydrophobically modified, ethoxylated aminoplast).…”
Section: Introductionmentioning
confidence: 99%